1996
DOI: 10.1002/pssa.2211530202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen in the (Fe1−xNix)4N compounds (0 ≤x ≤ 0.6)

Abstract: Single phase y'-Fe&-type (Fel_,Ni,)fi compounds and Fel-,Ni, (0 5 x 5 0.6) alloys are synthesized and studied by X-ray diffraction and Mossbauer spectroscopy. The structure changes from b.c.c. to f.c.c. when Fel_,Ni, (x 5 0.25) alloys are nitrided to (Fel-,Ni,)4N. The lattice expansion Aa/a is 5.3% for f.c.c. Fel-,Ni, alloys (x > 0.25) on nitrogenation. The observed decrease in the average iron hyperfine fields with nitrogenation, amounting to 8 to 14 T, is explained by the volume expansion and the chemical bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Therefore, the occupation preference of the nickel in the (Fe 1−x Ni x ) 4 N can be discussed by the high nickel substitution. This has been discussed in detail in the literature [13,16]. If the recoilless fraction of iron atom at every crystal site is the same, then we have the formula:…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, the occupation preference of the nickel in the (Fe 1−x Ni x ) 4 N can be discussed by the high nickel substitution. This has been discussed in detail in the literature [13,16]. If the recoilless fraction of iron atom at every crystal site is the same, then we have the formula:…”
Section: Resultsmentioning
confidence: 98%
“…This can be correlated to the alteration of local environment of the Fe atoms due to Cu atoms substitution and to the change of lattice parameters. However, the average isomer shift /ISS remains unchanged 0.28 mm/s for x ¼ 0.05 and 0.1 and increased to 0.35 mm/s for x ¼ 0.15 due to the change of the electronic configuration of the iron atoms [12]. If we suppose that the recoilless fraction of the iron atoms is the same at every crystal site, the Cu occupation preference is calculated by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the signals of their counterpart PSZIs shift 4±8 ppm to lower magnetic field. From the 29 Si and 1 H NMR of the PSZI-3 and PSZI-4, the Vi and Si-H contents decrease considerably, which might result from the reactions shown in Scheme 2 (n-BuLi and FeCl 3 might promote these reactions). The SiN-1, SiN-2, SiN-3, and SiN-4 samples are transparent liquids and can be easily dissolved in common .0 and 16.9 respectively.…”
Section: Synthesis and Characterization Of The Pszismentioning
confidence: 92%
“…For the 29 Si NMR of SiN-2 ( Fig. 2), signals in the range d À 3.8 to À8.1 are assigned to HN-SiMe 2 -NH, and d À 21 to À22.4 are assigned to (HN) 3 -SiMe; for the 29 Si NMR of SiN-3 (Fig. 2), signals in the range d À 3 to À7 are assigned to HN-SiMe 2 -NH, and d À 33 is assigned to (HN) 3 -SiVi.…”
Section: Synthesis and Characterization Of The Pszismentioning
confidence: 99%
See 1 more Smart Citation